Self-Heat of Freshly Harvested Grain (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
A powerful form of self-heating. The temperature rises to 50oC and above. The fluidity of the grain mass decreases. A strong blurring of the grain occurs. Some grains become moldy and start to rot. The grain has a strong rotten or unpleasant smell. Spontaneous heating of grain with low moisture during long storage. In practice, self-heating was observed as a result of long-term storage of grain mass with a moisture content lower than the critical moisture content.